Primary Packaging Design Development For Donutsmue As A Means To Increase Brand Awareness - Salsabilla, Nabilla Fitri; Retnoningsih, Sri (PT Ininnawa Paramacitra Edukasi, 2025)
In the era of modern competition, packaging design is one of the important elements in increasing the attractiveness and selling value of a product, especially for small and medium businesses in the food and beverage sector. Based on guidelines from the Indonesian Ministry of Cooperatives and SMEs, ideal packaging must contain complete information as a product identity and differentiator in addition to its function as a product protector. Donutsmue, a donut business that was established in 2021 and reopened in January 2025, still uses general packaging on the market without a clear brand identity. In fact, based on the results of interviews with the owner, the current marketing target is aimed at consumers aged 20 years and over who need attractive and informative packaging. This study aims to design Donutsmue's primary packaging design in three box sizes as a means of building brand awareness. The method used is descriptive qualitative, with primary data collection methods through interviews, observations, documentation, and distributing questionnaires to consumers. Secondary data was obtained from literature studies relevant to packaging design. The results of this study are in the form of a Donutsmue primary packaging design that emphasizes visual identity, values of togetherness, and a soft and sweet visual approach. This design is expected to strengthen the brand image and increase Donutsmue's competitiveness in the market.